'Doing the best we can': Registered Nurses' experiences and perceptions of patient safety in intensive care during COVID‐19. (20th August 2022) - Stayt, Louise Caroline; Merriman, Clair; Bench, Suzanne; M. Price, Ann; Vollam, Sarah; Walthall, Helen; Credland, Nicki; Gerber, Karin; Calovski, Vid
Abstract: Aims: To explore registered nurses' experiences of patient safety in intensive care during COVID‐19. Design: A qualitative interview study informed by constructivism. Method: Semi‐structured interviews were conducted and audio‐recorded with 19 registered nurses who worked in intensive care during COVID‐19 between May and July 2021. Interviews were transcribed verbatim and thematically analysed utilizing framework. Results: Two key themes were identified. 'On a war footing'—an unprecedented situation which describes the situation nurses faced, and the actions are taken to prepare for the safe delivery of care. 'Doing the best we can'—Safe Delivery of Care which describes the ramifications of the actions taken on short‐ and long‐term patient safety including organization of care, missed and suboptimal care and communication. Both themes were embedded in the landscape of Staff Well‐being and Peer Support . Conclusion: Nurses reported an increase in patient safety risks which they attributed to the dilution of skill mix and fragmentation of care. Nurses demonstrated an understanding of the holistic and long‐term impacts on patient safety and recovery from critical illness. Impact: This study explored the perceived impact of COVID‐19 on patient safety in intensive care from a nursing perspective. Dilution of skill mix, where specialist critical care registered nurses were diluted with registered nurses with no critical care experience, and the fragmentation of care was perceived to lead to reduced quality of care and increased adverse events and risk of harm which were not consistently formally reported. Furthermore, nurses demonstrated a holistic and long‐term appreciation of patient safety. These findings should be considered as part of future nursing workforce modelling and patient safety strategies by intensive care leaders and managers. No public or patient contribution to this study. The study aims and objectives were developed in collaboration with health care professionals.